2019
DOI: 10.1097/pep.0000000000000549
|View full text |Cite
|
Sign up to set email alerts
|

Moving Toward Excellence in Pediatric Physical Therapy Education: A Scoping Review

Abstract: Purpose: The purpose of this scoping review was to identify and map current evidence that underpins excellence in pediatric physical therapy education. Methods: An extensive review was conducted of literature published over a 27-year period regarding pediatric physical therapy/medical/allied health education. Results: Thirty articles were reviewed and analyzed. Articles were classified as levels of evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…A scoping review of pediatric physical therapy education reported a growing number of research studies, but these are primarily low-level evidence in the form of single institution case reports. 9 This knowledge gap is concerning because educators cannot compare the effectiveness of their current models of instruction with those employed by others to impact the overall quality of pediatric physical therapy training. 10 Positive or negative student outcomes from different instructional strategies may influence competency of entry-level physical therapists.…”
Section: Introduction and Purposementioning
confidence: 99%
See 1 more Smart Citation
“…A scoping review of pediatric physical therapy education reported a growing number of research studies, but these are primarily low-level evidence in the form of single institution case reports. 9 This knowledge gap is concerning because educators cannot compare the effectiveness of their current models of instruction with those employed by others to impact the overall quality of pediatric physical therapy training. 10 Positive or negative student outcomes from different instructional strategies may influence competency of entry-level physical therapists.…”
Section: Introduction and Purposementioning
confidence: 99%
“…The conclusion of the scoping review suggested educational research that focused on curriculum and teaching pedagogy with common assessment tools. 9 One possible outcome measure for pediatric physical therapy curricula is the Pediatric Communication and Handling Self-Efficacy Scale (PCHSES). 11 Self-efficacy (SE) is an individual' s belief in the ability to be successful in a behavior.…”
Section: Introduction and Purposementioning
confidence: 99%
“…Although this research addressed the specific population of pediatric physical therapy education, the use of a remote simulation to address interprofessional learning has merit to be generalized to related healthcare fields as interprofessional teamwork is essential to improve outcomes, quality, and safety of patient care (Joint Commission, 2015;WHO, 2010). Additionally, the findings underscored the importance of experiential learning as one of the main teaching and learning methods within pediatric physical therapy education (Anderson et al, 2019;Barta et al, 2018;Schreiber et al, 2015;Smith & Crocker, 2017). Students were generally satisfied with the simulated learning experience regardless of their age, race, or gender.…”
Section: Discussionmentioning
confidence: 80%
“…11,12 Despite the importance of experiential learning, the majority of pediatric education research involving ELOs has been of low methodological quality that consists of single institutional case study designs. 7,11,12,14 The lack of highquality research regarding pediatric ELOs is concerning and may partially be contributed to the variability in DPT pediatric education 8 and the limited number of reliable and valid student assessment instruments. 7 One reliable and valid student assessment instrument is the Physical Therapist Clinical Performance Instrument (PT CPI).…”
Section: Introductionmentioning
confidence: 99%